Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Suku Dinas Sosial Jakarta Timur - Pratiwi, Sevia Restu; Sari, Imelda (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Suku Dinas Sosial is responsible for providing services, supervision, and control (P3S) to solve social problems of people who have physical or mental limitations, so employees must work with high sensitivity and serve wholeheartedly. The purpose of this study is to determine the effect of work discipline (X_1) and work environment (X_2)on the performance of employees (Y) of Suku Dinas Sosial. In this study, a quantitative approach was used with questionnaire data collection techniques to obtain primary data for employees. The sample is 60 employees using the slovin technique. The results of this study found that work discipline (X_1) had a positive and significant effect on employee performance (Y) with a value of T_hitung4,525 >T_tabel2,002 with a level of significance 0,000 < 0,05. Partially, the work environment variable (X_2) has a positive and significant effect on employee performance (Y) with a value of T_hitung 4,757 >T_tabel 2,002 with a level of significance 0,000 < 0,05. Simultaneously the variables of work discipline (X_1) and work environment (X_2)have a positive and significant effect on employee performance (Y) with a value of F_hitung47,083 >F_tabel 3,16 with a level of significance 0,000 < 0,05.